Dinámica fiscal y comercial de Colombia: una mirada a partir de la ejecución del TLC con Estados Unidos (2018)
This article examines and analyzes the relationship between an open trade policy, the behavior of public finances and the economic growth of the country. The theoretical-conceptual points of view are contrasted, as references for the achievement of the proposed objective, with stylized data, in order to measure the effects: direct, indirect and elasticity, terms of trade, fiscal finances and Eco-nomic growth in the period 2000-2015. The dynamics of net exports, associated with their share of GDP and a comparison between the rates of evolution of the former and the second, led to the contribution of the external sector to the results of economic growth. In open economies such as the Colombian one, the external sector and public finances have a close articulation, since the former contributes resources to strengthen the finances of the State, according to the orientation of its policy. The empirical observation of the results of the tariff reduction and the collection of the external VAT, derived from the implementation of the FTA with the United States, allowed to determine its association with the fiscal behavior of the country in the analyzed period.